Granzyme B mediates impaired healing of pressure injuries in aged skin - Turner, Christopher T. (NPJ Aging Mech Dis, 2021)
Pressure injuries (PIs), also known as bedsores or pressure ulcers, are a major cause of death and morbidity in the elderly. The serine protease, Granzyme B (GzmB), contributes to skin aging and impaired wound healing. Aging is a major risk factor for PIs; thus, the role of GzmB in PI pathogenesis was investigated. GzmB levels in human PI tissue and wound fluids were markedly elevated. A causative role for GzmB was assessed in GzmB knockout (GzmB−/−) and wild-type (WT) mice using a murine model of PI. An apolipoprotein E knockout (ApoE−/−) model of aging and vascular dysfunction was also utilized to assess GzmB in a relevant age-related model better resembling tissue perfusion in the elderly. PI severity displayed no difference between young GzmB−/− and WT mice. However, in aged mice, PI severity was reduced in mice lacking GzmB. Mechanistically, GzmB increased vascular wall inflammation and impaired extracellular matrix remodeling. Together, GzmB is an important contributor to age-dependent impaired PI healing.